Pengaruh Literasi Keuangan Syariah, Fasilitas, Dan Kepercayaan Terhadap Minat Menabung Di Bank Syariah Bagi Masyarakat Pedesaan Nganjuk - Aprilia, Titin; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2024)
Nganjuk Regency is one of the regions where the majority of the population is Muslim, and it has a fairly strong economy, particularly in the agricultural sector, as it is one of the largest producers of shallots in East Java. The community requires financial institutions to manage their income. This study aims to determine the influence of Islamic financial literacy, facilities, and public trust on the interest in saving at Islamic Banks among rural communities in Nganjuk. The method used is quantitative research with an associative research type. Data analysis technique uses Partial Least Square (PLS-SEM). The research results show that the Islamic financial literacy variable has a positive and significant influence on interest in saving at Sharia Banks. Meanwhile, the facility and trust variables do not have a positive and significant effect on interest in saving at Sharia Banks. The results of this study indicate that improving financial literacy in Islamic banking can encourage interest in saving at Islamic Banks, particularly among the rural community in Nganjuk. Therefore, it is important for Islamic financial institutions to focus on Islamic financial education to enhance community participation in saving at Islamic banks, even though facilities and trust do not show a significant impact.